Inequality in the access to social housing in Cameroon: A decomposition of the poverty effect - Minfede koe Raoul (Universitas Negeri Malang, 2018)
This article studies the gap of access to social housing between the poor and the non poor in Cameroon. The data used is from the third Cameroonian survey of households (ECAM, 2007). We use the non linear decomposition model of inequalities. The results show a strong discrimination with regards to poor households. The differences in the access to social housing between the poor and the non poor are highly influenced by the distribution of variables such as: the residential area (61.22%), the income (34.18%), age (23,50%), the socio-professional category (22.39%) and the sector of activity (21.11%). These results put into question public policies on social housing.Keywords: Inequality, social housing, non-linear decomposition, the poorJEL Classification: H4, R2